Consumer Behavior Analysis In Shopping Decisions During The Covid-19 Pandemi - Besse Faradiba; Indrayani Indrayani (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Shopping decision is a process that starts from problem recognition and evaluates it to choosing the product that best suits oneself. This study aims to analyze the behavior of consumers who online (X1) or offline shopping (X2) as an independent variable that simultaneously effect the choice of purchase decision (Y) as the dependent variable during the covid 19 period. This research method use primary data in the form of a questionnaire. distributed to 50 respondents who frequently shopped both online and face to face during the Covid-19 pandemic. Testing the effect of independent variables on the dependent variable using multiple linear regression analysis techniques with SPSS. The results showed that the R box is 94.7%, which means that online shopping and direct shopping simultaneously had a positive effect on purchase decisions by 94.7%, while the remaining 5.3% is influenced by other variables not examined.